Social learning for understanding planning practices at the individual level - Bahrudin, Bahrudin; Ritonga, Mahyudin; Maseleno, Andino; Huda, Miftachul; Ibrahim, Mohd. Hairy (Linguistics and Culture Review, 2021)
Learning is a process of getting the knowledge to achieve better change. So people who learn need a process of guidance and direction to change their attitude and behavior to become independent human. In fact, most of people learn through selective observation and remember the behavior of other people in their environment. As has been done by the people who implement social learning program, the people have traditionally had local wisdom in protecting nature from generation to generation. This regulation has come a long way after the enactment of the government policy on natural protection of forest. As in the case of destroying forest, they will be subject to customary legal sanction in the form of fine which must be paid by someone as a form of apology.